Pengaruh Cita Rasa, Kualitas Pelayanan, dan Harga terhadap Keputusan Pembelian Mie Gacoan - Dewi Aprilia Nugraheni; Febryana Nawantoro; Rayhan Gunaningrat; R. Taufiq Nur Muftiyanto (Universitas Kristen Indonesia Toraja, 2024)
The rapid Indonesia's culinary industry is now developing at encouraging the emergence of many fast food restaurants. Mie Gacoan is a type of fast food restaurant whose basic ingredients are noodles. Mie Gacoan is a fast food restaurant whose basic ingredients are noodles. Mie Gacoan is one of the many choices of companies that are concerned with the culinary sector. This company distributes its products in spread outlets. This fast food restaurant serves spicy noodles at a level according to the consumer's choice as the main menu. Apart from that, they also offer side dishes with a choice of dimsum, shrimp spring rolls and various variations of drinks, of course these noodles are much loved by consumers in their teens. The purpose of this study is to ascertain how price, taste, and service quality affect consumers' decisions to buy gacoan noodles in Solo Baru. This study employed a quantitative methodology. Then, using non-probability selection procedures, researchers selected a sample of 100 respondents for this study. Members of the population or elements chosen as samples in this technique do not have the same opportunities and chances. A questionnaire was used to obtain the data. Multiple regression analysis was used in the data analysis process with IBM SPSS Statistics 25. The study's findings demonstrated that price had no bearing on judgments about purchases, service quality had a big impact on decisions about purchases, and taste had no bearing at all.